(untitled) (The Research of Medical Science Review, 2024)
Background: Pelvic surgeries are complicated in term of hemodynamic instability both during and after surgery, as it is an independent predictor of long-term patient morbidity and length of hospital stay. The development of hemodynamic instability is caused by a numerous factors. When these risk factors are prevented or treated, patients may experience less hemodynamic instability during pelvic surgery, as well as the morbidity and mortality that come with it in both spinal and general anesthesia. Objective: The objective of this study was to evaluate the factors that affect the hemodynamic stability and evaluate the effectiveness of different management strategies employed to ensure patient hemodynamic stability during spinal and general anesthesia.Method: A multicenter cross sectional study was conducted from August 2024 to November 2024 in KP. 172 adult patients undergone pelvic surgery were included in the study. Both the patient and surgical related factors were analyzed by SPSS. Frequencies, T test andbinary regression was used to correlate the factors and hemodynamic instability. The results were considered statistically significant with the p value < 0.05. Results: 53.5% of the patients had intraoperatively hemodynamic instability among them 59% of the patients were anaesthetize by general anesthesia and 44.8% by spinal anesthesia. Preload, type of pelvic surgery, prior medical history, ASA class II, preoperative medication, spinal anesthesia and extended procedure time were all associated with hemodynamic instability. Pharmacological management and fluid therapy employed to maintain the hemodynamic stability after instability paly important role.Conclusion: Hemodynamic instability was high with associated factors like preload, type of pelvic surgery, prior medical history, ASA class II, pre-medication and spinal anesthetic. To reduce the frequency of hemodynamic instability, it was advised that susceptible patients be closely monitored, that perioperative predictors of HDI be identified and treated early.